Recasting the agreements to re-humanize STEM education - Imad, Mays; Reder, Michael; Rose, Madelyn (Frontiers in Education, 2023)
The purpose of education is to understand and help address local and global problems to better society and the world. A key player in this endeavor should be STEM education, which has the potential to equip learners with the skills and knowledge necessary to address intersectional issues such as climate change, health and income disparities, racism, and political divisions. However, in this article we argue that despite the transformative potential of STEM education, it remains far removed from most people's lived experiences and is detached from the real-world social, political, and economic contexts in which it exists. This detachment not only perpetuates existing inequities by failing to meet the specific needs and reflect the experiences of these communities, but it also hampers STEM education's capacity to address the very local and global problems it is purported to solve. By remaining removed from the tangible, real-world contexts in which it exists, STEM education cannot fully harness its potential to better humanity. To address these issues, we propose humanizing STEM education by intentionally and explicitly grounding all work in the recognition of the inherent worth and dignity of all students, regardless of their background. We begin the article by critically examining the typically unspoken pre-existing assumptions or "agreements" that govern and dictate the norms of teaching and learning within STEM, ways of approaching framing STEM education that we often take for granted as necessary and true. We propose new agreements that expand the ways in which we think about STEM education, in hopes of making STEM education more accessible, inclusive, relevant, responsive, and reparative. Throughout, we deliberate on the notion of being human. We argue that to envision a future of humanistic STEM, one that is intentionally grounded in an ethics of care and equity for all, including the environment, it is necessary to continue to make visible and reimagine the unarticulated assumptions that underlie our current approaches to STEM education and practice.